Highway engineering. - Rogers, Martin (John Wiley & Sons Ltd, 2016)
Summary: "Highway Engineering provides an introduction to highway engineering for students on degree and diploma courses in civil engineering. The text moves in a logical sequence from the planning and economic justification for a highway, through the geometric design and traffic analysis of highway links and intersections, to the design and maintenance of both flexible and rigid pavements."--BOOK JACKET.